Un carnet inédit de croquis de Jean-Baptiste Pillement au Musée du Prado - CÉLINE GALY (Boletín del Museo del Prado)
The Museo del Prado houses an exceptional sketchbook of landscapes by the French artist Jean-Baptiste Pillement (1728-1808). Containing 34 drawings in black chalk made during his travels around Europe, it demonstrates the creative process of this artist, who assembled a repertoire of picturesque motifs which he subsequently employed, sometimes many years later, to compose his paintings. A detailed analysis of the motifs in the sketchbook, in particular the rocky cliffs and imposing rocks framing a waterfall, as well as the watermark of the paper, suggest that it dates from 1780 to 1800.